Amino acids as highly efficient modulators for single crystals of zirconium and hafnium metal–organic frameworks. Issue 18 (11th February 2016) - Marshall, Ross J.; Hobday, Claire L.; Murphie, Colin F.; Griffin, Sarah L.; Morrison, Carole A.; Moggach, Stephen A.; Forgan, Ross S.
Abstract : Addition of small quantities of amino acids to solvothermal and microwave syntheses of Zr and Hf MOFs drastically improves their crystallinity to the extent that single crystal structures can be obtained. Abstract : The synthesis of zirconium and hafnium metal–organic frameworks (MOFs) often relies on coordination modulation – the addition of competing monotopic modulators to reaction mixtures – to reproducibly generate highly crystalline material. Typically, large excesses of monocarboxylic acids such as formic, acetic and benzoic acid are applied, but access to diffraction quality single crystals, particularly of UiO-66 topology MOFs, remains troublesome. Herein, we show that amino acids, in particularl -proline, are highly efficient modulators of Zr and Hf MOFs of the UiO-66 series, with as little as four equivalents affording access to large, diffraction quality single crystals that are free of defects. Five crystal structures are reported, including MOFs which previously could not be characterised in this manner, with molecular dynamics simulations utilised to understand dynamic disorder. Additionally, a series of MOFs are characterised in depth, allowing a comparison of the thermal stabilities and porosities for Zr and Hf analogues. We also show that the protocol can be extended to microwave synthesis, and that modulating ability varies dramatically across a series of amino acids. Access to single crystals has facilitated our own in depth study of the mechanical properties of these MOFs, and we expect that our protocols will enable the discovery of new Zr and Hf MOFs as well as offer new insights into their materials properties.